I got to have this by Thursday
Let n = one of the number and m = the other number. You have two unknowns (m and n), so you need two equations to solve for the unknowns.
- The sum of two numbers is 15: n + m = 15
- The difference of the same numbers is 7: n - m = 7 (Therefore n = 7 + m)
Substitute n = 7 + m from the second equation in place of n in the first equation:
n + m = 15 [Equation 1]
7 + m + m = 15 [Substituted 7+m in place of n]
Solve for m.
Once you have m, solve for n using n = 7 + m from equation 2.